The effectiveness of videoscribe as innovative media to increase students reading comprehension - Roudatus Sarifah; Siti Maria Ulfa (English Teaching Journal : A Journal of English Literature, Language and Education, 2020)
The purpose of this study was to find out the effect of using videoscribe media learning on students' reading comprehension. We can create the content of reading use videoscribe with combine text and image in one video, so teaching learning proses doesnt monotonous and student can enjoyed to read. So it can help improved students reading comprehension. The design of this study was Pre-Experimental design. Thus, one classrooms containing the total of 15 students of eight grade at SMP AN NUR FUADI Bangkalan were selected as the sample. In collecting the data, pre-test and post-test were utilized to assess students’ comprehension abilities before and after the treatment. In analyzing the data, the t-tests (paired sample, and independent sample) were run in SPSS. The result is score post-test students is higher than pre-test score of studets. So the researcher conclude videoscribe media can applied in teaching reading to help teacher improved students reading comprehension.